Structural strengthening of RC buildings for enhanced seismic resistance - Güneş, B.; Coşgun, T.; Mangır, Atakan; Sayın, B. (Springer Science and Business Media Deutschland GmbH, 2021)
This study aims to present a strengthening technique for the seismic resistance of existing reinforced concrete (RC) buildings subjected to earthquake effects. The entire process is illustrated with a case study of an existing RC building. In this study, the building is examined with field surveys and numerical analyses. In the first stage, the damage assessment of the building was done with visual inspection and observation of structural members, and then the seismic performance of the examined RC building was determined using a nonlinear analysis method. Accordingly, a strengthening technique is comprehensively presented for this building, which was determined to be seismically insufficient. The enhancement achieved for the sufficient seismic strength is discussed by numerical comparisons considering the analysis results of the structural model that includes the strengthening members proposed in the presented technique. The presented research is important in terms of the numerical determination of the current state of similar RC buildings against the seismic effects, and to verify the feasibility of the proposed strengthening technique.
Keywords: Field Study; Numerical Analysis; RC Building; Seismic Performance; Strengthening